Synergy of oxygen and a piranha solution for eco-friendly production of highly conductive graphene dispersions. Issue 2 (2nd December 2014) - Savaram, Keerthi; Kalyanikar, Malathi; Patel, Mehulkumar; Brukh, Roman; Flach, Carol R.; Huang, Ruiming; Khoshi, M. Reza; Mendelsohn, Richard; Wang, Andrew; Garfunkel, Eric; He, Huixin
Abstract : An ecofriendly approach for graphene fabrication is developed, where no toxic and metal containing compounds were used and no toxic byproducts were generated. Abstract : A variety of strategies for the synthesis of solution processable graphene sheets has been developed so far. However, no approach has been reported to directly produce highly conductive, low-oxygen-containing graphene sheets without relying on toxic reagents and metal containing compounds and without generating toxic by-products. With an aim of developing such an eco-friendly approach, for the first time, this work studied solution phase oxidation of graphite particles and reversible graphite intercalation compounds using molecular oxygen and piranha etching solutions. We found that the synergy of the piranha etching solution and the intercalated molecular oxygen enables controlled oxidation of graphite particles assisted by microwave heating. The controlled oxidation leads to the rapid and direct generation of highly conductive, "clean", and low oxygen containing graphene sheets without releasing toxic gases or aromatic by-products as detected by gas chromatography-mass spectrometry (GC-MS). These highly conductive graphene sheets have unique molecular structures, different from both graphene oxide and pristine graphene sheets. It is even different from chemically reduced graphene oxide, while combining many of its merits. They can be dispersed in both aqueous and common organic solvents without surfactants/stabilizers, producing "clean" solution phase graphene sheets. "Paper-like" graphene films are generated via simple filtration, resulting in films with a conductivity of 2.3 × 10 4 S m −1, the highest conductivity observed so far for graphene films assembled via vacuum filtration from solution processable graphene sheets. After 2 hours of low temperature annealing at 300 °C, the conductivity further increased to 7.4 × 10 4 S m −1 . This eco-friendly and rapid approach for the production of highly conductive and "clean" solution-phase graphene sheets would enable a broad spectrum of applications at low cost.